1995
DOI: 10.1111/j.1365-2141.1995.tb03306.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment with interferon‐α2b for severe pruritus in patients with polycythaemia vera

Abstract: Pruritus is a major clinical problem in patients with polycythaemia vera (PV). Conventional symptomatic treatment is unsatisfactory. Recently, a favourable effect of interferon-alpha on pruritus in patients with PV has been reported. Also, interferon-alpha suppresses the increased haemopoiesis in PV. However, long-term treatment with interferon-alpha may be hampered by side-effects and the inconvenience of chronic subcutaneous injection therapy. We conducted a long-term study (median follow-up 13 months) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 13 publications
6
45
0
Order By: Relevance
“…In contrast, recent studies have suggested a greater than 50% response rate in PVassociated pruritus treated with paroxetine (20 mg/day), which is a selective serotonin reuptake inhibitor [84]. Other treatment modalities that have been reported to be useful in PV-associated pruritus include JAK inhibitors [85], interferon-a (IFN-a) [86] and narrow-band ultraviolet B phototherapy [87] Recommendations in the management of low-risk ET or PV without extreme thrombocytosis…”
Section: Management Of Low-risk Pv or Et In The Absence Of Extreme Tmentioning
confidence: 99%
“…In contrast, recent studies have suggested a greater than 50% response rate in PVassociated pruritus treated with paroxetine (20 mg/day), which is a selective serotonin reuptake inhibitor [84]. Other treatment modalities that have been reported to be useful in PV-associated pruritus include JAK inhibitors [85], interferon-a (IFN-a) [86] and narrow-band ultraviolet B phototherapy [87] Recommendations in the management of low-risk ET or PV without extreme thrombocytosis…”
Section: Management Of Low-risk Pv or Et In The Absence Of Extreme Tmentioning
confidence: 99%
“…Twelve of 15 patients with severe PV-associated pruritus showed significant improvement with IFN-a therapy [41]. Eight of 13 (61AE5%) patients with intractable itching reported a ‡ 50% reduction of pruritus 2-8 weeks after starting IFN-a [11].…”
Section: Management Of Pv-associated Pruritusmentioning
confidence: 99%
“…Studies of selective serotonin NA Not available reuptake inhibitors, specifically paroxetine, have shown greater than 50 % response rates in PV-associated pruritus [3,14,20]. Other treatment modalities that have been reported to be useful in PV-associated pruritus include JAK inhibitors [3,9,11,14], IFN-α [32], and narrowband ultraviolet B phototherapy [21], while response to both hydroxyzine and antihistamines in PV-associated pruritus has been more variable [3,9]. There is less published data regarding treatment options and their effectiveness for patients with PMF and pruritus.…”
Section: Discussionmentioning
confidence: 97%